Pengaruh Akuntabilitas Terhadap Kinerja Baitul Mal Kota Banda Aceh - Auliana Putri; M. Rizal Yahya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The main objective of this research is isvestigate the effect of accountability on Baitul Mal performance.This research uses corelational method, while the unit of observation is muzakki of Baitul Mal. The Type of data is primary data collected by a questionnare. Validity and reabiliy tests have also been done on the entire collected questionnaire. this research instruments containing interval scale for measurement, then hypothesis test are done using SPSS 20. The result of the research has shown that: (1) simultaneously, there is a significant effect of financial accountability, benefits accountability, and procedural accountability on Baitul Mal performance. (2) partially only benefits accountability and procedural accountability has significant effect on Baitul Mal performance. Where as financial accountability does not have significant effect on it.Keywords— financial accountability, benefits accountability, procedural accountability, Performance, and Baitul Mal. The main objective of this research is isvestigate the effect of accountability on Baitul Mal performance.This research uses corelational method, while the unit of observation is muzakki of Baitul Mal. The Type of data is primary data collected by a questionnare. Validity and reabiliy tests have also been done on the entire collected questionnaire. this research instruments containing interval scale for measurement, then hypothesis test are done using SPSS 20. The result of the research has shown that: (1) simultaneously, there is a significant effect of financial accountability, benefits accountability, and procedural accountability on Baitul Mal performance. (2) partially only benefits accountability and procedural accountability has significant effect on Baitul Mal performance. Where as financial accountability does not have significant effect on it